Proof: By Induction
(related to Proposition: Nth Difference Operator)
- By hypothesis, $f:D\to\mathbb R$ is a function with $D\subseteq\mathbb R.$ Moreover, let $n\in\mathbb N,$ $x, x+1,\ldots, x+n\in D.$
- The statement can be proved by induction.
- Base case $n=1$
- Induction step $n\to n+1$
- Inductin premise: Assume $n\ge 1$ and let the formula $$\Delta^m f(x)=\sum_{k=0}^m f(x+k)\cdot (-1)^{m-k}\cdot\binom mk$$ be true for all $m\le n.$
- By the induction step premise, and basic calculations involving the difference operator (no. 1 and no. 2) it follows $$\begin{align}\Delta^{n+1} f(x)&=\Delta (\Delta^n f(n))\\
&=\Delta\left( \sum_{k=0}^n f(x+k)\cdot (-1)^{n-k}\cdot\binom nk\right)\\
&=\sum_{k=0}^n(f(x+k+1)-f(x+k))\cdot (-1)^{n-k}\cdot\binom nk\\
&=\sum_{k=0}^n f(x+k+1)\cdot (-1)^{n-k}\cdot\binom nk-\sum_{k=0}^n f(x+k)\cdot (-1)^{n-k}\cdot\binom nk\\
&=\sum_{k=0}^n f(x+k+1)\cdot (-1)^{n-k}\cdot\binom nk+\sum_{k=0}^n f(x+k)\cdot (-1)^{n+1-k}\cdot\binom nk\\
\end{align}$$
- Changing the index $k+1\to k$ in the left sum allows combining both sums together:
$$\begin{align}
&=\sum_{k=1}^{n+1} f(x+k)\cdot (-1)^{n-(k-1)}\cdot\binom n{k-1}+\sum_{k=0}^n f(x+k)\cdot (-1)^{n+1-k}\cdot\binom nk\\
&=f(x+n+1)+\sum_{k=1}^{n} f(x+k)\cdot (-1)^{(n+1)-k}\cdot\binom n{k-1}\cdot \binom nk+f(x)\cdot (-1)^{n+1}\\
\end{align}$$
- With the recursive formula for the binomial coefficient, it follows
$$\begin{align}&=f(x+n+1)+\sum_{k=1}^{n} f(x+k)\cdot (-1)^{(n+1)-k}\cdot\binom {n+1}{k}+f(x)\cdot (-1)^{n+1}\\
&=\sum_{k=0}^{n+1} f(x+k)\cdot (-1)^{(n+1)-k}\cdot\binom {n+1}{k}.
\end{align}$$
∎
Thank you to the contributors under CC BY-SA 4.0!
- Github:
-
References
Bibliography
- Piotrowski, Andreas: Own Research, 2014